Postoperative morbidity following Whipple’s procedure for periampullary carcinoma: a retrospective study spanning 5 years - V., Sharath Kumar; J. S., Ajith Prasad (International Journal of Research in Medical Sciences, 2019)
Background: The morbidity rates for Whipple’s procedure has remained high even as mortality rates were coming down. This study was intended to assess postoperative morbidity rates in a tertiary care centre and to compare it with other centres. Methods: Data was collected from various registers and medical records for this retrospective cohort study. All Whipple’s procedures for 5 years were included in the study. Statistical analysis was done using R statistical software and the results were tabulated. Results: There were 48 patients and half of them developed morbidity. Surgical site infection was the most common complication (18.8%) followed by pulmonary complications (12.5%) and bile leak (6.25%). Half of the patients having pulmonary complications died while nobody with surgical site infection or bile leak died. Conclusions: In this study the morbidity rates were comparable to other centres. Hypoalbuminemia is a significant predictor of morbidity. Surgical site infection was the most common morbidity. Pulmonary complications were the most common cause for death. Morbidity rate is comparable to other centres and Whipple’s procedure is a safe surgery in the tertiary centre where the study was conducted.